(untitled) (Heritage, 2021)
After the exile from Spain in the 15th century, the Sephardim set out to seek refuge in other countries. That is how they came to the Balkans and built more communities on the territory of today’s Serbia. In order to adapt and cooperate with the local population, the Sephardim were active in the public sphere, being educated and learning the Serbian language. On the other hand, the female part of the Sephardic population was for many years exclusively related to the household and the family. Over time, women gained more rights and opportunities for emancipation and education, and the Sephardic women began to change their previous social role. In this regard, the aim of the paper is to present a brief overview of the arrival of Sephardim in today’s Serbia, to present some of the Sephardic communities, and then to draw attention to the position, role and education of Sephardic women, Women’s Jewish Society and how were emancipated Sephardic women in Belgrade, Novi Sad, Nis and Pirot.